Iranian nurses' perception of the public image of nursing and its association with their quality of working life - Fariborz Roshangar; Amin Soheil; Golshan Moghbeli; Taneal Wiseman; Hossein Feizollahzadeh; Neda Gilani (Nursing Open, 2021)
Abstract Aim To investigate the association between the nurses’ perception of the public image (PI) of nursing and the quality of nursing work life (QNWL). Design A descriptive correlational study. Methods 250 nurses of 12 hospitals affiliated with Tabriz University of Medical Sciences were sampled using a proportionate stratified sampling technique. Porter Nursing Image Scale and Brooks QNWL Scale were used for collecting data. Results There was a significant positive correlation between nurses’ perception of their public image and QNWL (r = .158, p = .012). Nurses’ perception of their PI along with other significant predictors including gender, age, position, work shifts, residency, financial status, level of family support, spouse's education and spouse's job significantly explained 15.2% of the predictability of QNWL (F(10,175) = 3.017, p = .001). Findings imply that enhancement of nurses' psychological status (nurses' perception of the public image of their profession) may improve their functional status (quality of nursing work life).